3
$\begingroup$

Why is the solution to the following PDE

$$au_x + bu_y = 0,$$ where $a$ and $b$ are both non-zero

$f(bx-ay)$ instead of $f(bx+ay)$?

I just do not understand the logic behind the solution.

$\endgroup$
  • 1
    $\begingroup$ The equation expresses the orthogonality of the function gradient to the vector $(a,b)$, i.e. parallelism to the vector $(b,-a)$. $\endgroup$ – Yves Daoust Jan 21 '15 at 21:12
2
$\begingroup$

The function $u^-(x,y) = f(bx-ay)$ solves $au_x+bu_y=0$, while $u^+(x,y) = f(bx+ay)$ doesn't, for the same reason that $x^+=3$ solves $4x-12=0$, while $x^-=-3$ doesn't - it's just a matter of plugging in.

In the equation $4x-12=0$, the symbol $x$ represents a number. Any solution to the equation is some number with the property that, if you plug that number in, you get a true statement. For example, $x=3$ solves the equation because $4\cdot3-12=12-12=0$. This happens to be the only solution, in this case. In particular, $x=-3$ is not a solution because $4(-3)-12=-12-12=-24\neq0$.

Similarly, in the equation $au_x+bu_y=0$, the symbol $u$ represents a function. A solution to the equation is a function with the property that, if you plug that function in, you get a true statement. For example, if $u(x,y) = f(bx-ay)$ then, by the chain rule, we get $$u_x = f'(bx-ay)b \: \text{ and } \: u_y = f'(bx-ay)(-a).$$ Thus, $$au_x+bu_y = af'(bx-ay)b + bf'(bx-ay)(-a) = abf'(bx-ay)-abf'(bx-ay)=0$$ but, if $u(x,y)=f(bx+ay)$, $$au_x+bu_y = af'(bx+ay)b + bf'(bx+ay)b = abf'(bx-ay)+abf'(bx-ay)\neq0.$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.